2005
DOI: 10.1007/s00167-005-0643-8
|View full text |Cite
|
Sign up to set email alerts
|

Symptomatic infrapatellar plica

Abstract: To assess the clinical outcomes of a group of patients who underwent arthroscopic infrapatellar plica (IPP) excision and to determine, whether the IPP was symptomatic or not, to identify the symptoms or signs in the patient's clinical presentation and to study the correlations between arthroscopic findings and patient's clinical presentation. A retrospective clinical study. We studied all the patients undergoing arthroscopic resection of symptomatic infrapatellar plica without other intraarticular abnormality … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
15
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(17 citation statements)
references
References 15 publications
2
15
0
Order By: Relevance
“…The origin of physiological noise varies and includes a buildup or bursting of tiny bubbles in the synovial fluid, snapping of ligaments, catching of the synovium or physiological plica, hypermobile meniscus or discoid meniscus, and perception of previous noise after knee surgery due to emotional concerns ( Table 1 ). 10 13 15 23 24 25 26 27) …”
Section: Causes Of Physiological Noisementioning
confidence: 99%
See 2 more Smart Citations
“…The origin of physiological noise varies and includes a buildup or bursting of tiny bubbles in the synovial fluid, snapping of ligaments, catching of the synovium or physiological plica, hypermobile meniscus or discoid meniscus, and perception of previous noise after knee surgery due to emotional concerns ( Table 1 ). 10 13 15 23 24 25 26 27) …”
Section: Causes Of Physiological Noisementioning
confidence: 99%
“…Other factors can also create physiological noise. Demirag et al 25) reported that the physiological popping or snapping was present in 72% of patients with infrapatellar plica. A young child under 10 years of age with a hypermobile or discoid meniscus has intermittent experiences of popping and snapping without obvious pain.…”
Section: Causes Of Physiological Noisementioning
confidence: 99%
See 1 more Smart Citation
“…The prevalence of synovial plicae ranges from 3% to 30% in western populations with most studies citing approximately 10% [ 1 ]. The inferior and superior plicae are the most common (50%–65%) with very little clinical relevance [ 2 ]. Mediopatellar plica is commonly symptomatic and is present at autopsies in one of the every three or four knees.…”
Section: Introductionmentioning
confidence: 99%
“…This clinical experience, spanning 28 years and hundreds of patients from 9-year-old children to elderly patients, is consistent with several reports in the literature of small numbers of patients in whom AKP has been relieved by release of the IPP at its FA. 23 , 31 , 32 , 33
Fig 1 Non-isometric mechanical behavior of infrapatellar plica (IPP), viewed arthroscopically (screenshots from Video 1 ). Arthroscopic views of the notch from the anterolateral portal (A-E) and anteromedial portal (F) are shown in the right knee of a 16-year-old patient with anterior knee pain for 4 years, with an insidious onset, undergoing release and resection of the IPP at its femoral attachment (FA).
…”
mentioning
confidence: 99%